Prefrontal space ratio in second‐ and third‐trimester screening for trisomy 21. (4th March 2013) - Yazdi, B.; Sonek, J.; Oettling, C.; Hoopmann, M.; Abele, H.; Schaelike, M.; Kagan, K. O.
ABSTRACT Objective To evaluate the prefrontal space ratio (PFSR) in second‐ and third‐trimester euploid fetuses and fetuses with trisomy 21. Methods This was a retrospective study utilizing stored mid‐sagittal two‐dimensional images of second‐ and third‐trimester fetal faces that were recorded during prenatal ultrasound examinations at the Department of Prenatal Medicine at the University of Tuebingen, Germany and at a private center for prenatal medicine in Nuremberg, Germany. For the normal range, 279 euploid pregnancies between 15 and 40 weeks' gestation were included. The results were compared with 91 cases with trisomy 21 between 15 and 40 weeks. For the ratio measurement, a line was drawn between the leading edge of the mandible and the maxilla (MM line) and extended in front of the forehead. The ratio of the distance between the leading edge of the skull and the leading edge of the skin (d1) to the distance between the skin and the point where the MM line was intercepted (d2) was calculated. The PFSR was determined by dividing d2 by d1. Results In the euploid and trisomy 21 groups, the median gestational age at the time of ultrasound examination was 21.1 (range, 15.0–40.0) and 21.4 (range, 15.0–40.3) weeks, respectively. Multiple regression analysis showed that PFSR was independent of maternal and gestational age. In the euploid group, the mean PFSR was 0.97 ± 0.29. In fetuses with trisomy 21, the mean PFSR was 0.2 ± 0.38 (P < 0.0001). The PFSR was below the 5th centile in 14 (5.0%) euploid fetuses and in 72 (79.1%) fetuses with trisomy 21. Conclusion The PFSR is a simple and effective marker in second‐ and third‐trimester screening for trisomy 21. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.